Prevalence and epidemiological characteristics of sports injuries: A comparative analysis of injured vs non-injured athletes - Fredianto, Meiky; Ulfa, Maria (UIR Press, 2024)
Background Problems: Sports exercise offers numerous health benefits but is also linked to sports injuries. According to a large body of research, researchers have identified age, gender, injury history, and level of competition as consistent risk factors for injury. Research Objectives: This study aims to analyse the injury prevalence of athletes in some sports and compare the epidemiological characteristics related to injury risk factors between athletes who experienced injuries and those who did not. Methods: This study employed a quantitative approach with a retrospective cross-sectional design. An online questionnaire collected data from a sample of 172 athletes and sports activists in football, cycling, and running. We conducted descriptive and comparative analyses using the SPSS 29 version. Findings and Results: 135 of the 172 respondents experience injuries, with the highest prevalence in football (42.2%), running (36.3%), and cycling (21.5%). Most athletes had recurrent injuries (36.3%). The Mann-Whitney test results showed no significant differences in mean age, weekly training frequency, and training duration between athletes who had injuries and those who did not. Conclusion: This study provides important insights into the prevalence and characteristics of injuries among athletes. The results of this study, which compare injured and non-injured athletes, can help develop better injury prevention and management strategies. We recommend increased awareness of injury conditions among athletes, coaches, and medical professionals to ensure a safe return to sport.